2015
DOI: 10.1186/s11671-015-0962-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and SERS Properties of Silver Nanorod Array Films Fabricated by Oblique Thermal Evaporation at Various Substrate Temperatures

Abstract: Aligned silver nanorod (AgNR) array films were fabricated by oblique thermal evaporation. The substrate temperature during evaporation was varied from 10 to 100 °C using a home-built water cooling system. Deposition angle and substrate temperature were found to be the most important parameters for the morphology of fabricated films. Especially, it was found that there exists a critical temperature at ~90 °C for the formation of the AgNR array. The highest enhancement factor of the surface-enhanced Raman scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 35 publications
1
21
2
Order By: Relevance
“…Coupled with their FDTD calculations, it was found that the pores formed from deposition at 140 K to generate hotspots for SERS enhancement which is consistent with their experimental observations. This suggests that making SERS substrates at lowered temperatures will generate greater enhancements, however, the opposite was found to be true in the study by Oh et al [43]. In their study, it was found that substrates made at higher temperatures had higher SERS enhancements than substrates made at lower temperature.…”
Section: Temperature Dependent Oblique Angle Depositioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Coupled with their FDTD calculations, it was found that the pores formed from deposition at 140 K to generate hotspots for SERS enhancement which is consistent with their experimental observations. This suggests that making SERS substrates at lowered temperatures will generate greater enhancements, however, the opposite was found to be true in the study by Oh et al [43]. In their study, it was found that substrates made at higher temperatures had higher SERS enhancements than substrates made at lower temperature.…”
Section: Temperature Dependent Oblique Angle Depositioncontrasting
confidence: 48%
“…The effect of substrate temperature has been a topic of interest for SERS researchers, particularly those using the oblique angle deposition configurations [16,43,59]. Compared to other materials typically used in OAD, silver and gold tend to have significantly lower surface diffusion activation energies, this means adatoms can more readily take part in thermally activated effects.…”
Section: Temperature Dependent Oblique Angle Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Raman scattering enhancement is attributed to the generation of local electromagnetic field "hotspots", due to the surface roughness of the materials and the shape of nanoparticles, coupled with LSPR excitation [16]. In fact, the high curvature surface, irregular surface and sharper edges exhibit a great enhancement of the Raman scattering by generating a local high electromagnetic field enhancement, demonstrating the importance of metal nanoparticles synthesis [11,12,16,17]. In this sense, silver nanostars, nanocubes, prisms, or nanoparticles with defects have demonstrated high sensitivity and high enhancement of the Raman signals showing higher potential, with respect to spherical nanoparticles with the same dimensions [12,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…20 A detailed study of morphology and SERS response of the AgNR array substrates fabricated at various substrate temperatures are presented elsewhere. 18 The crystallinity of a fabricated AgNR array was studied by investigating the obtained XRD spectrum presented in nature with a stronger (111) phase suggesting dominant out-of-plane growth along this crystal orientation. 21 Thus, these Ag nanorods fabricated via thermal evaporation technique are free from crystallographic contaminations as no counterfeiting diffraction is observed.…”
Section: Morphology Of Agnr Arraysmentioning
confidence: 99%